Hemocyte coagulation and phagocytic behavior in early stages of injury in crayfish (Arthropoda: Decapoda) affect their morphology - Mengal, Kifayatullah; Kor, Golara; Kouba, Antonín; Kozák, Pavel; Niksirat, Hamid (Developmental and comparative immunology, 2023)
Crustacean hemocytes are important mediators of immune functions such as coagulation and phagocytosis. We employed an in situ approach to investigate the ultrastructural behavior of hemocytes during coagulation and phagocytosis in the early stages after injury caused by leg amputation, using transmission electron microscopy technique in marbled crayfish Procambarus virginalis. Hemocytes underwent drastic morphological changes during coagulation. The morphology of the cytoplasmic granules changed from electron-dense to electron-lucent forms in an expanding manner. The transformed granules containing amorphous electron-lucent material were observed to merge and discharge their contents into extracellular space for coagulation. We also observed that the contents of the nucleus participate in the process of coagulation. In addition, leg amputation induced extensive muscle degeneration and necrotic tissues were avidly taken up by the phagocytic hemocytes containing distinct phagosomes. Interestingly, we observed for the first time how the digested contents of phagocytized necrotic tissues are incorporated into granules and other cellular components that change the cell morphology by increasing the granularity of the hemocytes. Nevertheless, the degranulation of hemocytes during coagulation can also reduce their granularity. Given that morphological traits are important criteria for hemocyte classification, these morphological changes that occur during coagulation and phagocytosis must be taken into account.
Keywords: Phagocytosis; hemocyty; fagocytóza; severní raci; členovci; Animals; Arthropods; Phagosomes; Astacoidea; fagozomy; zvířata; Hemocytes